2021
DOI: 10.3390/plants10122820
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Plant Regeneration, Genetic Uniformity, and Flow Cytometric Analysis of Regenerants in Rutachalepensis L.

Abstract: Ruta chalepensis L., an evergreen shrub in the citrus family, is well-known around the world for its essential oils and variety of bioactivities, indicating its potential medicinal applications. In this study, we investigated the effect of different culture conditions, including plant growth regulators, media types, pH of the medium, and carbon sources, on in vitro regeneration from nodal explants of R. chalepensis. Following 8 weeks of culture, the highest percentage of regeneration (96.3%) and maximum number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 106 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…This result supports the assertion that a proper balance between cytokinins and auxins forms a synergistic effect that induces in vitro proliferation of shoots [26]. Previous studies demonstrated that a relatively higher concentration of cytokinins in combination with lower concentrations of auxins promote in vitro cell division and induce the formation of a greater number of shoots per explant compared to using cytokinins alone [8]. This effect could be explained by the aforementioned synergistic effect between auxins and cytokinins along with their roles in the cell cycle and their significant effects on different phases of cell division and multiplication cycle.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result supports the assertion that a proper balance between cytokinins and auxins forms a synergistic effect that induces in vitro proliferation of shoots [26]. Previous studies demonstrated that a relatively higher concentration of cytokinins in combination with lower concentrations of auxins promote in vitro cell division and induce the formation of a greater number of shoots per explant compared to using cytokinins alone [8]. This effect could be explained by the aforementioned synergistic effect between auxins and cytokinins along with their roles in the cell cycle and their significant effects on different phases of cell division and multiplication cycle.…”
Section: Discussionsupporting
confidence: 88%
“…The overexploitation of M. crassifolia for medicinal purposes and as fodder coupled with the slow growth of the tree raises the need for a rapid and efficient means of propagation. Tissue culture enables the controlled growth and significant multiplication of plants from very small explants of the plant, e.g., hypocotyls, segments of roots, leaves, or stems, on an artificial medium [8], and therefore becomes an integral part of plant biotechnology. This technique has been successfully applied to the propagation of several important and endangered plant species [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was shown that low doses of BA (5.0 µM) had the highest probability of generating shoots from callus, with a greater response and number of induced shoots than higher doses (>5.0 µM). High dosages of cytokinin have been demonstrated to have deleterious effects on the multiplication of shoots in a range of plant species [20,33]. In a number of species, including Ruta graveolens [18], Citrus jambhiri [34], Notopterygium incisum [32], and Mondia whitei [35], BA has been shown to be highly effective in inducing shoot buds from callus mass.…”
Section: Discussionmentioning
confidence: 99%
“…Faisal, et al [19] reported regeneration through the shoot tip meristems of R. graveolens by cytokinin-auxin synergism. In vitro multiplication of R. chalepensis through direct regeneration was recently reported by Qahtan, et al [20].…”
Section: Introductionmentioning
confidence: 85%
“…Conversely, the low absorption efficiency of NAA makes it unsuitable for the regeneration of some plant tissues, as it could potentially lower rooting efficiency in culture [71]. In addition, it leads to callus development at the end cut of microshoots of Hebe buchananii, Hebe canterburiensis [72], and Ruta chalepensis [73]. However, NAA showed efficacy in stimulating root formation in vitro in clones of Ficus carica.…”
Section: Effect Of Auxins Concentrations On In Vitro Rooting Of F Pal...mentioning
confidence: 99%